2021
DOI: 10.1080/13696998.2021.1917139
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of nivolumab in squamous and non-squamous non-small cell lung cancer in Canada and Sweden: an update with 5-year data

Abstract: Aims: Nivolumab has been approved for advanced squamous and non-squamous non-small cell lung cancer (NSCLC) following platinum-based chemotherapy in both Canada and Sweden. We aimed to determine the value-for-money of nivolumab versus docetaxel in a Canadian and Swedish setting based on 5-year data. Methods: These cost effectiveness analyses used partitioned survival models with three mutually exclusive health states: progression-free, progressed disease, and death. All clinical parameters were derived from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…From a Chinese healthcare system perspective, our previous cost-effectiveness analysis revealed that second-line nivolumab was unlikely to be cost-effective compared with docetaxel in patients with advanced NSCLC, despite the subgroup analysis showing the improved cost-effectiveness of nivolumab in the patients with PD-L1TPS ≥1% ( 12 ). Although this finding did not concur with the cost-effectiveness analyses conducted in other countries showing a favorable cost-effectiveness of nivolumab versus docetaxel in previously treated advanced NSCLC patients regardless of PD-L1 expression ( 13 , 14 ), different perspectives, trial source used for analysis, and approach to modeling used between these studies have to be highlighted that may explain the inconsistency. Considering that nivolumab is recommended as the preferred second-line treatment for advanced NSCLC patients without ALK or EGFR mutations regardless of their PD-L1 expression in China, evidence regarding the impact of PD-L1 test results on the comparative cost-effectiveness of second-line nivolumab versus docetaxel from a Chinese health system perspective is urgently needed to inform Chinese healthcare policy making.…”
Section: Introductioncontrasting
confidence: 81%
“…From a Chinese healthcare system perspective, our previous cost-effectiveness analysis revealed that second-line nivolumab was unlikely to be cost-effective compared with docetaxel in patients with advanced NSCLC, despite the subgroup analysis showing the improved cost-effectiveness of nivolumab in the patients with PD-L1TPS ≥1% ( 12 ). Although this finding did not concur with the cost-effectiveness analyses conducted in other countries showing a favorable cost-effectiveness of nivolumab versus docetaxel in previously treated advanced NSCLC patients regardless of PD-L1 expression ( 13 , 14 ), different perspectives, trial source used for analysis, and approach to modeling used between these studies have to be highlighted that may explain the inconsistency. Considering that nivolumab is recommended as the preferred second-line treatment for advanced NSCLC patients without ALK or EGFR mutations regardless of their PD-L1 expression in China, evidence regarding the impact of PD-L1 test results on the comparative cost-effectiveness of second-line nivolumab versus docetaxel from a Chinese health system perspective is urgently needed to inform Chinese healthcare policy making.…”
Section: Introductioncontrasting
confidence: 81%
“…The use of external data is particularly useful when only limited trial follow-up data is available, as they can provide validation of the resulting extrapolations for survival probabilities and hazard rates from short-term data [13]. Such an approach was previously taken in relation to the CheckMate-017 and CheckMate-057 cost-effectiveness models used in HTA submissions, where external validation of parametric models was carried out using NSCLC data from the longer term Phase I trial CheckMate-003, as well as longer term data from the US National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) program and the national cancer registries of Sweden and Norway [12,[14][15][16][17][18]. The nivolumab OS parametric models used in these cost-effectiveness models are herein referred to as 'validated SPMs', whereas those that do not leverage external data are referred to as 'non-validated SPMs' for the purpose of this research.…”
Section: Methodsmentioning
confidence: 99%
“…In this previous work, dependent and independent parametric models were considered by BMS in model selection, although the focus of this paper is restricted to the nivolumab arm. Validated SPMs were those used in cost-effectiveness models submitted to NICE and other HTA bodies and later published in peer-reviewed journals, and were selected conservatively to avoid criticism by the ERG and other HTA reviewers [14][15][16][17][18].…”
Section: Model Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations